1980
DOI: 10.1002/pssb.2220970212
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Jahn‐Teller Coupling Constants of 3d Transition metal Ions in Crystals. I. General Theory

Abstract: A method is proposed for the calculation of the Jahn-Teller coupling constants for orbitally degenerated states of ions in crystals based on the applicat,ion of perturbation theory in adiabatic potential matrix caIcuIation. The cluster approximation and LCAO-MO scheme are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Indeed, taking the values g i = −300 cm −1 (Ref. 45) and V e , a, and c like before 41 we found that for a Mn-Mn pair in the ac-plane the minimum of the total energy U z−z = H ij z−z + g i cos 3ϕ i + g j cos 3ϕ j is shifted away from ϕ i = −2π/3 and ϕ j = 2π/3 towards ϕ i = −ϕ j = 113 • . The corresponding energy coupling per one pair is −485 cm −1 , i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, taking the values g i = −300 cm −1 (Ref. 45) and V e , a, and c like before 41 we found that for a Mn-Mn pair in the ac-plane the minimum of the total energy U z−z = H ij z−z + g i cos 3ϕ i + g j cos 3ϕ j is shifted away from ϕ i = −2π/3 and ϕ j = 2π/3 towards ϕ i = −ϕ j = 113 • . The corresponding energy coupling per one pair is −485 cm −1 , i.e.…”
Section: Resultsmentioning
confidence: 99%
“…7 X ⌫ are symmetric orbital operators, acting on the 3d-t 2g triplet, and V ␣ ͑␣ = e , t , a , b , c͒ and V ␣ R ͑␣ = e , t͒ are electron-lattice coupling constants. 26,27 The expressions in the first two square brackets, which are H lin and H QQ , represent interactions of the Ti 3+ 3d-t 2g electron with the linear and quadratic symmetrized shifts of the oxygen octahedron correspondingly, and H R ͑the third expression͒ is responsible for this electron and a cube of R ions shifts coupling.…”
Section: Orbital Ground Statementioning
confidence: 99%
“…26,27 For each constant V ␣ any of the above-mentioned Qs with appropriate ⌫ may be used. For example, V e is equal to ‫͗ץ‬H vib ͘ / ‫ץ‬Q and also to ‫͗ץ‬H vib ͘ / ‫ץ‬Q ⑀ .…”
Section: Orbital Ground Statementioning
confidence: 99%
“…where the index k numbers all of the copper ions in the unit cell and the symmetrized coordinates Q θ , Q characterize the e g distortion of the oxide octahedra around the copper ions (for more details, see [10]). Evaluation of the linear Jahn-Teller coupling constant V e for the CuO 6 cluster with the distance R(Cu-O) = 0.21 nm (the average Cu-O distance in La 2 CuO 4 ) with the aid of the method of [14] gives V e = −2.5 nN.…”
Section: The Modelmentioning
confidence: 99%